Perlindungan Hukum Terhadap Pengetahuan Tradisional Di Indonesia - Prasada, Erisa Ardika (Universitas Muhammadiyah Palembang, 2022)
Traditional knowledge is part of society that is passed down from generation to generation and needs to be protected by law. There is potential for economic benefits resulting from the use of traditional knowledge by developed countries through biopiracy or misappropriation. This article aims to examine the legal protection for people who possess traditional knowledge from acts of biopiracy or misappropriation under the Patent Law (UU Patent). The research method in writing is normative research with a statutory approach. The results of the study reveal that the legal protection of traditional knowledge is regulated in Article 26 of Law no. 13 of 2016 concerning Patents, namely if the invention relates to and/or originates from genetic resources and/or traditional knowledge, it must clearly and correctly state the origin of the genetic resources and/or traditional knowledge in the description. This is done so that genetic resources and/or traditional knowledge are not recognized by other countries and in order to support Access Benefit Sharing (ABS). The distribution of results and/or access to the use of genetic resources and/or traditional knowledge is carried out in accordance with the laws and regulations and international agreements in the field of genetic resources and traditional knowledge.Keywords: Benefit Sharing; Patent; Traditional Knowledge